Enhancing the Cognitive Level of Novice Learners Using Effective Program Writing Skills - Yalagi, Pratibha S.; Indi, Trupti S.; Nirgude, Manisha A. (2016 International Conference on Learning and Teaching in Computing and Engineering (LaTICE), 2016)
Computer programming subject is a core ingredient for most of the engineering disciplines. However for the first year engineering, teaching and learning fundamentals of programming language like C has been considered as a great challenge to both teachers and novice learners. The challenges in learning the programming languages are: the learners are not able to analyze the flow of program, cannot fix errors or not able to debug the program, usually dependent on others for problem solving, bug fixing. Programming skills and documentation are the most important aspects of software development. The structure of C program with proper indentation, comments & proper named variables can reduce most of the general compiler errors. The study proposes a novice way of teaching C language programming with effective program writing skills for the beginners. The experiment is conducted for the First year Civil engineering students and the course is Computer Programming based on C language. A training session on effective program writing skills is conducted, to improve the ability of program writing skills with minimized compiler errors for novice learners. The effect of the experiment is verified with Pretest & Posttest before and after the training session. It is observed that the program written with proper indentation, comments and proper named variable can reduce the number of compiler errors and more than 60% of the student have written & executed the given C programs successfully in a stipulated time.